Evaluation of the productive response of male cattle to the substitution of corn grain by different levels of fresh sweet potato tuber (Ipomoea batatas L.) in a fattening diet - Ruiloba, M. H.; Maure, J.; Solis, C. (Cuban Journal of Agricultural Science, 2021)
The productive response to the substitution of milled corn grain by fresh sweet potato tuber (I. batatas) in a ration destined to fattening steers was evaluated. A completely random design with a 3 x 2 factorial arrangement was used. The study lasted 78 days and three substitution levels were evaluated on a dry basis: 0, 50 and 100 % (TL0, TL50 and TL100, respectively), and two evaluation periods. The diets were isoenergetic and isoprotein. A total of four crossbreed males, with an average initial weight of 358 + 23 kg were used per treatment. The live weight gain was 1.620, 1.670 and 1.756 kg animal day-1 for TL0, TL50 and TL100. The intake of dry matter, fresh tuber and crude protein was 2.66, 2.67 and 2.76 kg; 0.00, 0.76 and 1.56 kg DM; 0.303, 0.296 and 0.305 kg; while the metabolizable energy intake resulted 29.50, 29.16 and 29.00 MJ 100 kg of live weight day-1 and the food conversion, 6.88, 6.68 and 6.62 kg of dry matter intake per kg of live weight gain-1 for TL0, TL50 and TL100. The cost of the fresh sweet potato tuber and the substitution of the milled corn grain was 0.18 and 0.40 kg dry-1 (US dollars). With respect to TL0, the feeding cost was reduced by 18.0 and 28.3 % with TL50 and TL100. It is concluded that the fresh sweet potato tuber proved to be a competitive and economically viable nutritional alternative, as an energy source for the replacement of 100 % of the corn grain in diets for fattening male cattle. Key words: Tainung 66, sweet potato tuber, weight gain, intake, food conversion, feeding cost